Maximum Height of Maxillary Air Sinus in Adult Bangladeshi Population (Bangladesh Journal of Anatomy, 2024)
Background: Size and shape of the maxillary air sinus varies from person to person and two maxillary air sinuses may have different patterns in the same individual. The study aimed at radiological measurement of maximum height of maxillary air sinus in adult Bangladeshi population. The study findings will be helpful for diagnosis and therapeutic procedures related to maxillary air sinus. Materials & Methods: A cross sectional analytical type of study was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka from July 2019 to June 2020. The study population were 90 Bangladeshi (male 45 and female 45) attending the Radiology & Imaging Department of Sir Salimullah Medical College. The maximum height of the right and left maxillary air sinuses were measured by joining the upper and lower limit of right and left maxillary air sinuses by using “MB RULLER” software. Results: The maximum height of right maxillary air sinus was significantly higher (< 0.05) than the maximum height of left maxillary air sinus in male. There was no significant difference between right and left maxillary air sinuses in female. No significant difference was observed in the maximum height of right and left maxillary air sinuses of male and female. Conclusion: The maximum height of right maxillary air sinus was higher than the maximum height of left maxillary air sinus in male.Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 1, pp. 17-21